Pengaruh Konflik Peran, Kelelahan, dan Pelatihan Auditor terhadap Kualitas Audit - Ricky Bryan D.P. Tampubolon (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
This study aims to examine the effect of role conflict, fatigue, and training on audit quality among auditors in the Jakarta area. The research sample consisted of 148 internal and external auditors with a minimum of two years of work experience. Data were collected through questionnaires and analyzed using multiple linear regression to determine the relationship between the independent and dependent variables. The results show that role conflict and fatigue have a negative and significant effect on audit quality, while training has no significant effect. The research model explains 62.5% of the variation in audit quality, with the remaining portion influenced by factors outside the model. These findings confirm that psychological factors and auditors’ workload play a more dominant role in determining the quality of audit results compared to the training provided. The practical implication of this study is that audit organization management needs to focus on human resource management strategies that can reduce role conflict and decrease auditors’ fatigue levels. In addition, existing training programs should be evaluated and redesigned to be more applicable, relevant to job demands, and equipped with effective learning transfer mechanisms, so they can make a tangible contribution to improving audit quality.